ANALISIS 4K KARYAWAN TENAGA PENDIDIK - Edi Siregar (Jurnal Manajemen, 2021)
The research was conducted to test and analyze the effect of competence, commitment and compensation on employee performance. This study used a survey method with a questionnaire as the main instrument. The populations of this study were 89 employees, with a census method where all members of the population were sampled. Data analysis was performed using regression analysis, hypothesis testing through f test and t test. The results of the analysis found that there is a significant relationship and influence both partially and simultaneously between competence, commitment and compensation with employee performance